EXERCISE CAPACITY AND MORTALITY RISK IN A WIDE AGE SPECTRUM COHORT OF 750, 302 VETERANS. (June 2022) - Pittaras, Andreas; Faselis, Charles; Doumas, Michael; Grassos, Haralampos; Stavropoulos, Konstantinos; Imprialos, Konstantinos; Papavasiliou, Maria; Manolis, Athanasios; Myers, Jonathan; Kokkinos, Peter
Abstract : Objective: Most studies that have evaluated the association between exercise capacity and the risk of all-cause mortality have focused on middle-aged Caucasian populations. We assessed mortality risk associated with fitness in male and females across a wide spectrum of age (30–95 years) and ethnicities. Design and method: In this retrospective cohort study, we included male and female Veterans who completed an exercise treadmill test (ETT) between 1999–2020. We assigned participants to one of ten age-specific fitness categories based on peak metabolic equivalents (METs) achieved during the ETT. The primary endpoint was all-cause mortality adjusted for age, body-mass index, ethnic origin, sex, cardiovascular disease, cardiovascular risk factors and medications. We assessed mortality from Veterans Affairs records up to Dec 31, 2020. We compared groups with Cox proportional hazard model. Results: We assessed 750, 302 Veterans, ages 30–95 years (mean 61.3 years, SD 9.8 years). During a median follow-up of 9.8 years (IQR 5.6–14.0), 164, 288 died with an average yearly mortality rate of 22 deaths per1, 000 person-years. The exercise capacity-mortality risk association was independent, inverse, and graded for all ages, ethnicities, and men and women. Compared to the least fit group for each age decile, mortality risk was 50% lower at peak exercise capacities of approximately 10.0 METs for those 30–49 years, 8.0 METs for septuagenarians, and 7.0 METs for octogenarians. The lowest mortality risk was observed at approximately 14.0 METs with no additional decline or increase in risk beyond this level. Being unfit, defined having exercise capacity below the median (<8.5 METs), was associated with > 2 times higher mortality risk compared to fit (>8.5 METs), and was higher than the risk of the traditional cardiac risk factors examined. Conclusions: Higher Exercise Capacity is independently associated with lower mortality risk for all ages, ethnicities, and gender. An exercise capacity < 8.5 METs carried a greater risk than that of the traditional cardiac risk factors. Approximately 50% lower risk was noted in all age categories, commensurate to an exercise capacity achievable by most individuals within a given age category.